Clothing purchase habits and how it affects the willingness to buy convertible clothing a study on selected women working in Makati City - Encabo, Hazel P.; Morales, Anna Leticia E. (2010.)
ABSTRACT The study focused on the current clothing purchase habits of selected women working in Makati City. Specifically, it determined how such habits affect their willingness to buy convertible clothing, Factors which are considered important when it comes to a working woman's garment spending and what aspects of her life influence those choices were also analyzed.
A descriptive survey method with the use of a questionnaire was conducted to meet the objectives of the study applying purposive sampling. 101 female employees in Makati were selected as respondents based on the following criteria: (1) willingness to participate in the study; (2) must be females; and (3) must be currently employed in a private corporation in the Makati Central Business District. Through the data gathered in the survey an analysis of both quantitative and qualitative data was used to infer trends and general opinions of the respondents on the factors they consider in their clothing purchases as well as on convertible clothing.
Results showed that 82% of the respondents were more inclined to buy expensive garments with high quality than cheaper ones of lower grade. Among all the considerations, style and design was what they valued most in a garment purchase followed by price. It was also seen that younger women tend to spend more of their monthly income on clothing and from varied demographical information, their spending was diversified dependent on age, income and the number of children a woman had.
When it comes to convertible clothing, results suggested that the factors that women look for are its styles and versatility, Those who already own these types of garments are found to be more conscientious spenders and are meticulously looking at more features prior to purchasing it. Theses women were also more likely to be willing to buy convertible clothing in the future rather than those who are not owners of this type of garment. And though multifunctionality is the primary selling point of convertible clothing, women still considered other factors such as style, comfort, price, and quality before purchasing it.
With these findings, further research of a limited market of women can enhance an in-depth analysis of their preferences. Also, a broader, more random and less constrained population can test the conclusions on a bigger scale to give supplemental data to the marketers of convertible clothing.
Thesis (B.S. Clothing Technology)--University of the Philippines Diliman.
Keywords: Consumer behavior -- Philippines; Clothing habits